Spinal Cord Stimulation Explantation and Chronic Pain: A Systematic Review and Technology Recommendations - Wahezi SE; Yener U; Naeimi T; Lewis JB; Yerra S; Sgobba P; Ciftci HB; Vydyanathan A; Chiu E; Cherkalin D; Darji JY; Masterson R; et al. (Journal of Pain Research)
Sayed E Wahezi,1 Ugur Yener,1 Tahereh Naeimi,1 Joshua B Lewis,1 Sandeep Yerra,1 Philip Sgobba,2 Hatice Begum Ciftci,3 Amaresh Vydyanathan,2 Elisa Chiu,1 Denis Cherkalin,4 Jay Y Darji,5 Ryan Masterson,6 Danielle Lee,7 Atthakorn Jarusriwanna,8 Suwannika Palee,9 Nicole R Ortiz,10 Moorice Caparo,1 Eli Dayon,11 Camille Fontaine,2 Marom Bikson,12 Michael E Schatman,13 Scott G Pritzlaff,14 Timothy R Deer,15 Corey W Hunter16 1Department of Physical Medicine & Rehabilitation, Montefiore Medical Center, Bronx, NY, USA; 2Department of Anesthesiology, Montefiore Medical Center, Bronx, NY, USA; 3Physical Medicine and Rehabilitation, ROMMER International Physical Therapy and Rehabilitation Medical Center, Bursa, Turkey; 4Pain Management, New York Spine Specialist, New York, NY, USA; 5Pain Management, Regenerative Spine and Pain Institute, Plainsboro Township, NJ, USA; 6Pain Management, Old Mill District Clinic, Summit Health, Bend, OR, USA; 7Department of Neurology, Hackensack University Medical Center, Hackensack, NJ, USA; 8Department of Orthopaedics, Faculty of Medicine, Naresuan University, Phitsanulok, Thailand; 9Department of Rehabilitation Medicine, Faculty of Medicine, Naresuan University, Phitsanulok, Thailand; 10Pain Management, Sage Pain & Wellness Institute, San Diego, CA, USA; 11Department of Physical Medicine & Rehabilitation, Burke Rehabilitation Hospital, White Plains, NY, USA; 12Department of Biomedical Engineering, the City College of New York, New York, NY, USA; 13Department of Anesthesiology, Perioperative Care and Pain Medicine, Department of Population Health – Division of Medical Ethics, NYU Grossman School of Medicine, New York, NY, USA; 14Department of Anesthesiology and Pain Medicine, University of California, Davis, CA, USA; 15The Spine and Nerve Center of the Virginias, West Virginia University Hospitals, Charleston, WV, USA; 16Ainsworth Institute of Pain Management, Department of Rehabilitation & Human Performance, Icahn School of Medicine at Mount Sinai, New York, NY, USACorrespondence: Sayed E Wahezi, Department of Physical Medicine and Rehabilitation, Montefiore Medical Center, 1250 Waters Place, Tower #2  8th Floor, Bronx, NY, 10461, USA, Tel +1 718-920-7246, Fax +1 929-263-3950, Email swahezi@montefiore.orgBackground: Chronic pain affects 20.5% of the US population, costing $296 billion annually in lost productivity. Spinal cord stimulation (SCS) has become a key treatment for refractory neuropathic and nociceptive pain, with increasing usage due to technological advancements. However, the durability of SCS therapy, including explantation rates, remains a concern. Understanding explantation causes is essential for improving patient selection and device effectiveness. This study aims to analyze SCS explantation rates and reasons, as well as evaluate the financial burden of these procedures on the healthcare system.Methods: Three primary screening methods were used: manual search with keywords, MeSH term query, and reference list screening. The search covered PubMed, Cochrane, and Web of Science databases from inception to November 2024, yielding 719 articles. After applying eligibility criteria, 72 articles were identified, and 25 were selected for analysis. Data extraction was done by independent reviewers, with a second reviewer ensuring accuracy. Discrepancies were resolved by the corresponding editor.Results: We reviewed data from 13,026 patients who underwent permanent SCS implantation between 1984 and 2024, across 25 studies. A total of 1882 patients (9.82%) underwent explantation. The most common reason was lack of efficacy and inadequate pain relief (38%), followed by lead failure (15%) and infection (14%). While SCS is generally effective, issues related to device longevity and patient satisfaction persist, with explantation rates due to technical failures and lack of efficacy being concerns.Conclusion: SCS efficacy varies, with explantation rates reaching up to 38%, often due to inadequate pain relief. Most explantations occur within the first year, despite SCS being a safe and effective treatment. High implantation costs ($35,000 to $70,000) and revision costs ($15,000 to $25,000) raise concerns among payors. The hardware-driven model limits waveform flexibility, highlighting the need for innovation.Keywords: chronic pain, spinal cord stimulation, explantation, implant removal, cost-effectiveness